PENGARUH HARGA, KUALITAS PELAYANAN DAN LOKASI TERHADAP KEPUASAN TAMU PADA HOTEL PURI BAGUS CANDIDASA KARANGASEM (Fakultas Ekonomi Universitas 17 Agustus 1945 Surabaya, Indonesia, 2024)
This research was conducted based on the phenomenon of the assessment of guests who were dissatisfied with the types of services available, for example cleanliness, comfort, food, service and price, but there are types of services that consumers feel satisfied with and are always a reason to stay at Hotel Puri Bagus Candidasa, for example the location. Some of these deficiencies resulted in the ups and downs of the number of guests who came to the Puri Bagus Candidasa Hotel. The purpose of this study was to determine and analyze the effect of price, service quality and location on guest satisfaction at Hotel Puri Bagus Candidasa Karangasem, either partially or simultaneously. The sampling technique used in this study was proportional random sampling by taking a sample of 20% of the population so that the respondents in this study were 80 people. The test results simultaneously (Test F) Price, Service Quality and Hotel Location together have a positive and significant effect on guest satisfaction at Hotel Puri Bagus Candidasa Karangasem. Partial test results (t test) Price has a positive and significant effect on Guest Satisfaction at Hotel Puri Bagus Candidasa Karangasem means that if the price is increased, guest satisfaction will increase. The partial test results (t test) Service Quality has a negative and insignificant effect on Guest Satisfaction at Hotel Puri Bagus Candidasa Karangasem, meaning that if the service quality decreases, guest satisfaction will not increase. Partial test results (t test) Location has a positive and significant effect on Guest Satisfaction at Puri Bagus Candidasa Hotel Karangasem, meaning that if the location is more strategic, guest satisfaction will increase. The result of the Determination Coefficient (R2) test shows that 0.499 means 49.9% Guest Satisfaction can be explained by Price, Service Quality and Location. Meanwhile, the other 50.1% is explained by other variables not discussed in this study. Keywords: Price, Service Quality, Location, Satisfaction